A study of safety and effectiveness of amino-acids based multi-nutrient fortifier in preterm infants - Chandra, Prathap; Sharma, Deepa M.; Gowda, Suresh; L., Ramitha; Kamath, Laxmi (International Journal of Contemporary Pediatrics, 2024)
Background: Fortification plays a vital role in supporting the nutritional requirements in the premature infants. Currently in India, fortifiers are either whole protein based or whey protein which are bovine milk- based, which has been associated with increased risk of feed intolerance and necrotizing enterocolitis (NEC), to circumvent this, an amino-acids based fortifier has been made available which provides more proteins (0.35 g/1 g sachet) thereby meeting the nutritional requirements of preterm infants. Aim was to study effect (safety and efficacy) of fortification with the amino-acids based fortifier (HMF-ADVANCE, Analeptik Biologicals) in premature infants admitted in the neonatal intensive care unit (NICU). Methods: A single centre pilot study was conducted on preterm infants with <1800 g birth weight and/or <32 gestational age, amino-acids based fortifier (AABF) was used as the fortification option once the infants reached 100 ml/kg/day feed volume. 1 g of HMF-ADVANCE was mixed in 25 ml of mother’s own milk (MOM) and the fortification was continued till discharge from NICU. Results: A total 100 preterm infants were included for the study, mean gestational age (GA) was 29.38±1.61 weeks, mean birth weight was 1159.90±301.9. Growth outcomes at the end of the study: mean weight gain was 23.73±7.62 g/day, mean head circumference gain was 1.02±0.41 cm/week, mean length gain was 1.01±0.15 cm/week and weight gain velocity were 17.13±2.38 g/kg/day. Blood urea nitrogen (BUN) showed an increasing trend from baseline (before starting fortification: 3.2 mg/dl), 1 week after fortification (6.3 mg/dl) and at the end of study (11.2 mg/dl). AABF was also used in three neonates post NEC. There were no episodes of feed intolerance or necrotising enterocolitis episodes and none of neonates discontinued fortification till discharge from NICU. Conclusions: AABF was well tolerated without any feed intolerance episodes and helped to achieve optimal growth. AABF can be the optimal choice of fortification in low-birth-weight neonates.